1991
DOI: 10.1007/bf01600246
|View full text |Cite
|
Sign up to set email alerts
|

Acute ascending necrotizing myelitis in Okinawa caused by herpes simplex virus type 2

Abstract: A case of rapidly progressing ascending myelitis was necropsied. Necrosis was present throughout the whole length of the spinal cord and involved both the grey and white matter randomly. The perivascular lymphocytic infiltration in the spinal cord in the present case was more pronounced than that in the previously reported two cases of necrotizing myelopathy associated with malignancy. Using immunoperoxidase staining the presence of herpes simplex virus type 2 (HSV 2) antigen was demonstrated. Electron microsc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
14
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 9 publications
2
14
0
Order By: Relevance
“…HSV-2 myelitis has occurred in patients with malignancy and diabetes, which suggests a certain predisposition in immunocompromised patients. [3][4][5][6][7] Among patients with HIV infection, only three cases of HSV-2 myelitis or myeloradiculitis have been reported, to our knowledge. [8][9][10] All three patients were severely immunocompromised.…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…HSV-2 myelitis has occurred in patients with malignancy and diabetes, which suggests a certain predisposition in immunocompromised patients. [3][4][5][6][7] Among patients with HIV infection, only three cases of HSV-2 myelitis or myeloradiculitis have been reported, to our knowledge. [8][9][10] All three patients were severely immunocompromised.…”
Section: Discussionmentioning
confidence: 80%
“…Most initial reports were based on postmortem diagnosis of patients who died as a consequence of ascending myelitis. [5][6][7][8]10 However, more recently, a favourable outcome after antiviral treatment has been reported in some patients, including one AIDS patient. 3,9,12 Our report supports the possibility of a non-fatal outcome of HSV-2 myeloradiculitis among HIV-infected patients, although neurological sequelae may undermine the patient's quality of life.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Cutaneous inoculation of HSV has been used to investigate the role of the immune system in prevention of the disease (Oakes 1975;Simmons & Hash 1984); however, there have only been a few reports of histological examination when this inoculation is given by alternative routes and when the disease manifests extracerebrally (McFarland et al 1986;Chrisp et al 1989;Sunagawa et al 1995). In this paper we have examined experimental myelitis using the HSV 2 strains isolated in Okinawa where viral characteristics have been reported previously Sunagawa et al 1995) and we have compared the histology with previously reported human cases (Iwamasa et al 1989(Iwamasa et al , 1991. There have been few such studies of experimental HSV myelitis (Dix & Mills 1985).…”
mentioning
confidence: 93%
“…Amplification was carried out at 94°C for five minutes, 55°C for 30 seconds and 72°C for one minute for one cycle followed by 94°C for 6 It has been suggested that dormant herpes simplex virus in the dorsal root ganglia is reactivated when the patient becomes immunocompromised.48 Thus the condition has been described in patients with diabetes mellitus48 as in the present case, the acquired immune deficiency syndrome,23 and various malignancies. 7 It is conceivable that cases of "idiopathic" transverse myelitis are caused by herpes simplex virus and that current tissue culture, electron microscopic, and immunological techniques, if performed, are unable to detect it.' The advent of the polymerase chain reaction has simplified and speeded up the diagnosis of herpes simplex virus encephalitis in those centres where the technique is available.9-"1 The technique should now be extended to those patients with an undiagnosed rapidly progressive cord syndrome in the hope that early diagnosis and treatment with acyclovir will carry a better prognosis.…”
mentioning
confidence: 99%